MEMAHAMI KONSEP METODE BLENDED LEARNING - Muthoharoh, Miftakhul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Education is currently facing extraordinary challenges since the existence of covid-19, learning that is usually done face-to-face has turned into learning that must be done remotely. Online learning requires teachers to innovate various learning methods. The blended learning method comes as one of the methods that can be applied during the Covid-19 pandemic. This research tries to examine the concept of blanded learning method. This research uses a type of library research (library research) with a literature review approach. based on the findings, the blanded learning method can be used as a learning method amid the Covid-19 conditions that have not subsided.